Clinical and molecular genetic findings of hereditary Parkinson's patients from Turkey. (December 2021) - Emekli, Inci; Tepgeç, Fatih; Samancı, Bedia; Toksoy, Güven; Hasanoğulları Kına, Gizem; Tüfekçioğlu, Zeynep; Başaran, Seher; Bilgiç, Başar; Gürvit, İ. Hakan and Emre, Murat and Uyguner, Zehra Oya and Hanagasi, Hasmet A.
Abstract: Introduction: The majority of Parkinson's disease (PD) ensue late-onset with a complex spectrum of environmental and genetic risk factors. Awareness of genetic causes in patients with PD is essential for genetic counseling and future genotype-oriented therapeutic developments. Methods: Large pathogenic changes in eight PD-related genes and small pathogenic sequence variants in 22 PD-related genes were investigated simultaneously in 82 PD patients from 79 families where clinical evaluations were performed. The phenotypic characteristics of the patients with molecular changes were examined for genotype-phenotype relations. Results: Pathogenic variants in SNCA, PRKN, DJ-1, FBXO7, and GBA genes were determined in 25 patients from 24 families (24/79, 30%). Associated variants were found in PRKN in 14, SNCA in three, FBXO7 in two, and DJ-1 in one patient. A novel homozygous deletion (c.491delT, p.(V164Dfs*13) (SCV001733595)) leading to protein truncation in the PRKN gene was identified in two patients from the same family. Furthermore, heterozygous GBA gene variants were detected in five patients from different families. Conclusion: It has been shown that the most common cause of genetically transmitted PD is the PRKN gene, while LRRK2 does not play an essential role in this selected population. It has been suggested that even if the autosomal recessive inheritance is expected, genes with autosomal dominant effects such as SNCA should not be overlooked and suggested for investigation. Our study is also the first for evaluating the pathogenic GBA variants' frequency in PD patients from Turkey. Highlights: PRKN is the most common cause of genetically transmitted PD in our selected population. Pathological GBA variants may play a role in the development of Parkinson's disease in Turkey. Genes with AD effects should not be overlooked in an AR inheritance pattern.